Substantial Deep‐Soil Carbon Losses Outweigh Topsoil Gains in European Beech Forests Since the 1980s - Mathias Mayer; Klaus Dolschak; Emilia Winter Artusio; Michael Grabner; Michael Tatzber; Iftekhar U. Ahmed; Elisabeth Wächter; Selina Türtscher; Leopold Lindebner; Isolde K. Berger; Pétra Berger; Wolfgang Wanek; et al. (Global Change Biology, 2025)
Soils are a major reservoir for organic carbon (C), with subsoils (> 20–30 cm soil depth) storing most of this C. Predicting the response of deep‐soil C to global change remains a critical research priority; yet long‐term field observations for forests are scarce. In this study, we assessed decadal C dynamics in mineral soils to 90 cm depth of 62 temperate mature stands of European beech ( Fagus sylvatica ) in Austria using data from sampling campaigns in 1984, 2012, and 2022. Our results show an increase in C stocks between 0 and 20 cm and a significant decrease in C stocks at 20–50 cm and 50–90 cm soil depth, suggesting substantial C losses from deep soils. These deep soil C losses outweighed the C gain in topsoils, resulting in a soil C loss of −0.44 ± 0.19 Mg C ha −1 year −1 since the 1980s. Organic‐rich calcareous soils appeared to be particularly vulnerable to C loss, while soils containing high amounts of iron and manganese were less affected, probably because they stabilize C more effectively. We suggest that changes in regional climate (i.e., warmer and wetter) and factors such as changes in litter inputs and rooting depth may underlie the observed patterns of depth‐dependent soil C changes. The estimated soil C loss accounted for 17% of the C accumulated in aboveground biomass over the same period, as determined by dendrochronological analysis, indicating a reduction in the ecosystem's C sink capacity since the 1980s. Our results highlight the importance of including deep‐soil C storage in forest ecosystem C cycle assessments, as it plays a key role in the overall ecosystem C balance.